Increase in hospital admissions for childhood asthma: trends in referral, severity, and readmissions from 1970 to 1985 in a health region of the United Kingdom. - Anderson, H R (1989)
Admissions to hospital for childhood asthma have continued to increase, but the reasons are unknown. Because the incidence of acute asthmatic attacks in the community greatly exceeds the admission rate, this increase could be a result of changes in medical practice shifting the balance of care towards the hospital without there being any underlying change in morbidity. In the South West Thames Region (population 2.9 million) over the eight years 1978-85 the number of hospital admissions among those aged 0-4 and 5-14 rose by 186% and 56%. A random sample of case notes from all hospitals in the region was examined for evidence of changes in mode of referral, severity on admission (duration of episode, vital signs on admission), and readmission ratio. The findings indicate that there has been no reduction in severity on admission or increase in readmission rate since 1978. The findings for the 5-14 age group contrast with those from an earlier study (1970-8) in the same region, in which a substantial increase in self referral was observed together with an increase in readmissions and a reduction in the duration of the attack; pulse and respiration rates on admission have, however, remained unchanged over the 16 year period. Overall, these findings indicate that the increase in admissions cannot be satisfactorily explained by changes in medical practice alone and may be due to an increase in the number of asthmatic children experiencing severe attacks. This points to a change in the epidemiology of childhood asthma.